#DeleteFacebook: From Popular Protest to a New Model of Platform Capitalism?. Issue 5 (3rd September 2021) - Mills, Stuart
ABSTRACT: In March 2018, a series of newspaper articles about the subversive use of the social media platform Facebook during various elections in 2016 were published. These revelations produced a backlash against the platform, which resulted in a popular hashtag, #DeleteFacebook . This article uses the # DeleteFacebook campaign as a case study to analyse the contemporary model of platform capitalism. Furthermore, by introducing emerging literature on data trusts – specifically, the notion of a bottom up data trust – this paper argues the # DeleteFacebook campaign reveals, both in its conception and in its ultimate failure, a desire for an alternative model of platform capitalism. By drawing on the # DeleteFacebook campaign, this article argues that a bottom up data trust designed to empower individual users can resolve many of the initial grievances, and barriers to success, experienced by the campaign.